Summary of Research: Efficacy of Trastuzumab Deruxtecan in HER2-Expressing Solid Tumors by Enrollment HER2 IHC Status: Post Hoc Analysis of DESTINY-PanTumor02 - Oaknin, Ana; Lee, Jung-Yun; Makker, Vicky; Oh, Do-Youn; Banerjee, Susana; González-Martín, Antonio; Jung, Kyung Hae; Ługowska, Iwona; Manso, Luis; Manzano, Aránzazu; Melichar, Bohuslav; Siena, Salvatore; et al. (Advances in therapy, 2025)
of the original article, 'Efficacy of Trastuzumab Deruxtecan in HER2-Expressing Solid Tumors by Enrollment HER2 IHC Status: Post Hoc Analysis of DESTINY-PanTumor02'. Trastuzumab deruxtecan (T-DXd) is an antibody-drug conjugate, which is a chemotherapy with a linker (deruxtecan) joined to an antibody (trastuzumab). Trastuzumab binds to the human epidermal growth factor receptor 2 (HER2) protein on cancer cells, where it releases the chemotherapy to kill these cells. The DESTINY-PanTumor02 clinical study tested the effectiveness of T-DXd for people with various HER2-expressing cancers and the safety of treatment. Previous results from DESTINY-PanTumor02 showed that T-DXd had antitumor activity, and the greatest effects were seen in people with the highest tumor level of HER2 [defined as immunohistochemistry (IHC) 3+]. In this previous analysis, the HER2 expression was measured at a central laboratory. In clinical practice, HER2 expression will likely be measured at a local laboratory, so understanding whether T-DXd has similar effects regardless of how HER2 expression is measured is important. Here, we looked at the effects of T-DXd based on the HER2 test result used to determine a person's eligibility for the study, which could be measured using a local or central laboratory. In people with IHC 3+ tumors (where HER2 was measured at a local or central laboratory), 51% had a decrease in the size or number of tumors, according to established criteria (referred to as an objective response), while, in people with IHC 2+ tumors, 26% had an objective response. Side effects with T-DXd were consistent with previous studies. These results confirm T-DXd has antitumor effects in HER2-expressing cancers where the HER2 expression is measured by a local or central laboratory.
Keywords: trastuzumab; Female; kamptothecin; výsledek terapie; ženské pohlaví; Neoplasms; nádory; klinické zkoušky, fáze II jako téma; Immunohistochemistry; lidé; Treatment Outcome; imunohistochemie; Receptor, ErbB-2; protinádorové látky imunologicky aktivní; HER2-expressing; imunokonjugáty; receptor erbB-2; HER2 testing; Secondary Data Analysis; Clinical Trials, Phase II as Topic; Trastuzumab deruxtecan; Advanced/metastatic solid tumors; Camptothecin; Trastuzumab; sekundární analýza dat; Immunoconjugates; Antineoplastic Agents, Immunological; Humans